Implementasi Akad Bagi Hasil dan Peningkatan Pendapatan Ekonomi Masyarakat Nelayan Di Kecamatan Camplong Sampang - Musoffan, Musoffan; Fahmi, Ainul; Holis, Moh. (Unversitas Islam Madura, 2024)
The purpose this study was to determine cooperation system between the boss and the fishermen and the implementation of the sharing of fish catches carried out by the boss to the fishermen and the increase in fishermen's income in Camplong. The research approach with qualitative research and descriptive analysis and data collection using the interview method. The results of the study showed that the implementation of profit sharing for fishermen in Camplong carried out a cooperation agreement between the boat owner and the worker in. The implementation of the profit sharing separately, is none other than using an agreement that has been determined by Islamic law. Meanwhile, the increase in fishermen's income is also supported by side businesses carried out by fishermen's wives who also work by developing household industries such as fish drying, fish processing, fish smoking, and other types of micro businesses.